Factors that influence job performance among employees in UiTM Dungun Terengganu / Nur Fathiah Omar, Rohaida Abdul Kelam and Syarifah Munyati Syed Ab Rahman - Omar, Nur Fathiah; Abdul Kelam, Rohaida; Syed Ab Rahman, Syarifah Munyati (2012)
This research study contain the purpose of study, methods, finding, conclusion and recommendations. The purpose of this study is to determine the factor that influence employees performance in UiTM Dungun, Terengganu. The factors that have been identified are training factor, work environment factor, motivation factor and lastly job characteristic factor. The finding shows the result from the questionnaire that has done or collected. The question were divided into three sections. Section A is to investigate the factors that influence job performance among employees in organization. Section B identified the important of job performance among employees in organization. Section C will be covered the demographic information of respondents such as gender, age, status, department, level of education, working experience and job categories. Besides that, the conclusions and recommendations discuss the results of the findings obtained from the questionnaires answered by the respondents and the recommendation for future research.